PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fariz Mustaqim; La Ode Abdul Rakhman; Ahmad Daholu (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research aims to determine the effect of corporate social responsibility (CSR) disclosure on company value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2021-2023. This research uses a simple linear regression method and descriptive analysis with a quantitative approach. The data collection method was carried out by looking at the financial reports and sustainability financial reports of each company used as a research sample and processed using the SPSS application. Based on the research results, it was concluded that partially the corporate social responsibility (CSR) disclosure variable had a significant effect on company value, as seen from the significance value of the t test results (partial test), namely with a significant value of 0.001 < 0.05. The resulting regression coefficient is 8.328, which is positive. This positive direction means that the corporate social responsibility (CSR) disclosure variable is directly proportional (in the same direction) to the company value variable. The value of the contribution determined through the results of the coefficient of determination test is 30.5%.